Anemia in remote interior communities in Sarawak, Malaysia - Dominic, Sagin; Molll, Mohamad; Ghazally, Ismail; OT, Sya (Southeast Asian Ministers of Education Organisation., 2002)
A cross-sectional survey of 365 individuals, (51.9% males, 48.1% females; ages 5-85 years), from five remote interior communities in upper Rejang River basin Sarawak, Malaysia, found 24.4% were anemic. The range and mean of Hb concentration in male and female were: 7.2-17.0 mg/ml and 13.7 mg/ml and 7.9-15.7 mg/ml and 12.9 mg/ml respectively. Amongst the five tribes surveyed, the prevalence of anemia (range: 10.6-46.7%), was higher among the Penans (46.7%), Kenyahs (31.1%), Kajangs (27.8%) and Kayans (19.3%), than amongst the Ukits (10.6%). Anemia is more common among males > 40 years and among adolescents and young reproductive females, as well as elderly females > 61 years old. Of the 83 anemic individuals, 6.0% and 3.6% had Trichuris trichiura or hookworm respectively; however there is no clear association with intestinal worm infection.